Analysis of Electrical Energy Demands in Friction Stir Welding of Aluminum Alloys. (2017) - Buffa, Gianluca; Campanella, Davide; Di Lorenzo, Rosa; Fratini, Livan; Ingarao, Giuseppe
Abstract: Manufacturing processes, as used for discrete part manufacturing, are responsible for a substantial part of the environmental impact of products. Despite that, most of metalworking processes are still poorly documented in terms of environmental footprint. To be more specific, the scientific research has well covered conventional machining processes, concerning the other processes there is a lack of knowledge in terms of environmental load characterization instead. The present paper aims to contribute to fill this knowledge gap and an energetic analysis of Friction Stir welding (FSW) is presented. Following the CO2PE! methodological approach, power studies and a preliminary time study have been performed in order to comply with the In-Depth approach. The influence of the most relevant process parameters is analyzed regarding the required FSW energy. Finally, a few potential improvement strategies to reduce FSW energy consumption are reported.